Implementasi Modul Komunikasi LoRa RFM95W Pada Sistem Pemantauan Listrik 3 Fasa Berbasis IoT - Ahmad Adhitya Nurhadi; Denny Darlis; Muhammad Ary Murti (Ultima Computing : Jurnal Sistem Komputer, 2021)
The use of electricity for large loads such as buildings and industry is a 3-phase electrical system. The manual activity of recording or monitoring data on electricity usage is considered impractical, so the use of IoT devices can be a solution. However, sending data on IoT devices using wired communication and Wi-Fi is considered less suitable considering that the device will be placed in a panel room that is rarely covered in the network. So that the use of other IoT communications such as LoRa can be an option. Therefore, the design and manufacture of LoRa-based IoT devices was carried out. This is done to expand the scope of IoT devices in carrying out 3-phase kWh meter readings. The device sends data through LoRa communication with test parameters, namely RSSI, SNR and throughput. The device made is an interface between a 3-phase kWh meter with LoRa communication which includes a MAX485 IC, ATMega 2560 microcontroller, and LoRa RFM95W communication module. From the test results, the device can send 3-phase kWh meter data every 3.611 seconds with an average throughput of 957.231 bps. LoRa communication performance used in LOS conditions can reach 300 meters with RSSI -107.625 dBm, SNR -13.063 dB. Meanwhile, in non-LOS conditions the lowest RSSI was -103.338 dBm and the lowest SNR was -8.897 dB.